Mobile Application with Augmented Reality for the Learning of the Cell - Tazza Alejos, Jean Carlo (2021)
This study shows the effects resulting from the implementation of a mobile application with augmented reality for the learning of the cell. The Mobile-D methodology was used for this study, whose focus and properties are mainly targeted at the mobile device market. The quasi-experimental design was used in a sample of 40 fifth-grade students from a private school in Lima, which was divided into two groups of 20 students: a control and an experimental group. And it was found the experimental group achieved a significant improvement in the learning level compared to the control. Lastly, it is concluded that the use of a mobile application with augmented reality has significantly improved in three aspects of learning.